PENGARUH TEGANGAN PERMUKAAN PADA TEBAL FILM CAIRAN DAN KARAKTERISTIK GELOMBANG ANTARMUKA ALIRAN DUA FASE STRATIFIED HORIZONTAL - Ari Prasetyo; Setya Wijayanta; Indarto Indarto; Deendarlianto Deendarlianto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
This experimental study aims to examine the effect of the surface tension on the characteristics of unidirectional air-liquid interface waves on a horizontal pipe. The pipe used is an acrylic pipe with a diameter of 26 mm. To vary the surface tension, the working fluid consisted of 100% water and water mixed with 2% and 5% butanol. with surface tension (σ) values ​​of 72, 58, and 42.5 mN/m, respectively. The wave characteristics studied in this research include the interface wave structure which is analyzed from visual observations and parameters by image processing. The superficial velocities of gas and liquid were varied in the range of 4-16 m/s and 0.02-0.1 m/s, respectively. Wave velocity and frequency were determined by using cross-correlation and power spectra density (PSD) from time-series data of liquid film thickness. Generally, velocity increases as the gas superficial velocity and surface tension decrease, the high gas superficial velocity the dominant frequency is high.